PILATES METHOD IN RESPIRATORY MUSCLES STRETCHING (Fiep Bulletin - online, 2014)
Introduction: Pilates method uses in an intense way the respiration, and therefore can alter respiratory muscles strength. Objective: to evaluate the benefits that the Pilates method promotes in respiratory function. Methodology: It treats of  a study of a semi experimental type with quantitative approaching. The sample was of 46 young adults, with ages from 18 to 30 years, of both sexes. It was carried out a height, weight, respiratory muscle strength, current volume, minute volume and slow vital capacity verification. Two groups were formed: eutrophic and overweight/obesity. Results: After the stretching were observed significant results in Pimax (p
Keywords: Stretching; Pulmonary Function; Pilates Method.